92 Brix as an Indicator of Energy Value in Alfalfa and Orchardgrass Herbage. (30th November 2020) - Soder, Kathy J; Billman, Eric D; Horst, Jeff; Balk, Kristi; Hafla, Aimee
Abstract: This study correlated Brix values (measure of total dissolved solids via refractometer) with wet-lab analyses (WLA) of sugar concentrations in fresh herbage of two forage species, alfalfa (ALF; Medicago sativa) and orchardgrass (ORG; Dactylis glomerata) to estimate energy value of pastures. Four monthly samplings occurred from May-August, 2019. At each sampling, eight ALF and ORG samples were collected from established monocultures of each species. Solubles were extracted from fresh herbage using a hand-held garlic press. Triplicate Brix readings were recorded per sample using a digital refractometer. Fresh herbage samples were flash-frozen in liquid N, freeze-dried, and analyzed via WLA for total and individual (glucose and fructose) sugar concentrations, as well as nutritive value (CP, NDF, and ADF; Agri-King, Inc., Fulton, IL). The TDN, RFV, and RFQ were calculated. Brix values were correlated with WLA using the PROC CORR procedure in SAS, with significance established at P < 0.05 and trends at 0.05 < P < 0.10. Brix values were negatively correlated (P < 0.001) with WLA of total sugars (-0.65), glucose (-0.6), and fructose (-0.68) in ORG while no significant correlations (P > 0.10) were detected in ALF. Conversely, Brix values of ORG and ALF were positively correlated (P < 0.01) with NDF (0.57 – 0.58) and hemicellulose (0.42 – 0.55), as well as with ADF in ALF (0.54). Brix was negatively correlated (P < 0.05) with CP in ALF (-0.41), but there was no correlation (P > 0.10) with ORG. No correlations (P > 0.10) were detected between Brix and TDN, RFV, and RFQ. These results indicate that the Brix index does not directly translate to forage quality, particularly sugar concentrations, of ALF and ORG, and may inadvertently select herbage with increased fiber concentrations. Producers should consider more accurate methods, such as WLA, for assessing energy value of pastures.